Dynamical evolution of Ge quantum dots on Si(111): From island formation to high temperature decay: Nanoscience: Special Issue Dedicated to Professor Paul S. Weiss. Issue 4 (22nd April 2022) - Preetha Genesh, Navathej; De Marchi, Fabrizio; Heun, Stefan; Fontana, Stefano; Belkhou, Rachid; Purandare, Rahul; Motta, Nunzio; Sgarlata, Anna; Fanfoni, Massimo; MacLeod, Jennifer; MacLean, Oliver; Rosei, Federico
Abstract: Heteroepitaxial growth is a process of profound fundamental importance as well as an avenue to realize nanostructures such as Ge/Si quantum dots (QDs), with appealing properties for applications in opto‐ and nanoelectronics. However, controlling the Ge/Si QD size, shape, and composition remains a major obstacle to their practical implementation. Here, Ge nanostructures on Si(111) were investigated in situ and in real‐time by low energy electron microscopy (LEEM), enabling the observation of the transition from wetting layer formation to 3D island growth and decay. The island size, shape, and distribution depend strongly on the growth temperature. As the deposition temperature increases, the islands become larger and sparser, consistent with Brownian nucleation and capture dynamics. At 550°C, two distinct Ge/Si nanostructures are formed with bright and dark appearances that correspond to flat, atoll‐like and tall, faceted islands, respectively. During annealing, the faceted islands increase in size at the expense of the flat ones, indicating that the faceted islands are thermodynamically more stable. In contrast, triangular islands with uniform morphology are obtained from deposition at 600°C, suggesting that the growth more closely follows the ideal shape. During annealing, the islands formed at 600°C initially show no change in morphology and size and then rupture simultaneously, signaling a homogeneous chemical potential of the islands. These observations reveal the role of dynamics and energetics in the evolution of Ge/Si QDs, which can serve as a step towards the precise control over the Ge nanostructure size, shape, composition, and distribution on Si(111). Abstract : Real‐time low energy electron microscopy observations reveal the growth dynamics and stability of Ge quantum dots formed on Si(111) at temperatures between 450°C and 600°C. A mix of metastable, flat islands and tall, faceted islands are produced at 550°C and below, whereas growth at 600°C yields uniform large, triangular islands.